(untitled) (Research, Society and Development, 2020)
In the scope of Science Teaching, it is possible to perceive the learning potentials developed with the students, resulting in changes in the school routine and in the practice of teachers, thus realizing the paths of training, of the evaluation processes about Science Teaching. For that, it is necessary to understand how Science Teaching happens in the basic school, specifically its limits and possibilities. In this study we aim to understand the configuration of Science Teaching during the students’ learning process and the practice of teachers from the early years of elementary school. This is an exploratory research with a qualitative approach, using, as theoretical foundations, the studies of Pimenta (1994), Freire (1996), Gasparin (2003) Kosik (2010). The results show the following limits: i) teachers’ embarrassment when the class does not achieve the expected results; ii) the need for greater articulation between Science Teaching and the reality of students, school and teachers; iii) the need for greater monitoring and pedagogical support for the results to be achieved; iv) the recurrence of training as a way of making students able to teach Science. Therefore, it is necessary that alternatives are created to minimize the gaps regarding Science Teaching, bringing it closer to the reality of the school, students, teachers, favoring quality education.